2005
DOI: 10.1111/j.1365-2893.2005.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of, and risk factors for, hepatitis C virus infection among recent initiates to injecting in London and Glasgow: cross sectional analysis

Abstract: Our aim was to compare the prevalence of antibody to hepatitis C virus (anti-HCV) among recently initiated injecting drug users (IDUs) in London and Glasgow, and to identify risk factors which could explain differences in prevalence between the cities. Complementary studies of community recruited IDUs who had initiated injection drug use since 1996 were conducted during 2001-2002. Data on HCV risk behaviours were gathered using structured questionnaires with identical core questions and respondents were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…While several studies have reported associations between HCV seroconversion and syringe sharing, many associations were relatively weak after controlling for other factors; other studies failed to find any association (38)(39)(40)(41). Sharing is highly correlated with behaviours driven by specific drug use patterns.…”
Section: Resultsmentioning
confidence: 99%
“…While several studies have reported associations between HCV seroconversion and syringe sharing, many associations were relatively weak after controlling for other factors; other studies failed to find any association (38)(39)(40)(41). Sharing is highly correlated with behaviours driven by specific drug use patterns.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of improved blood transfusion safety serotypes associated with blood transfusions are being replaced by other serotypes especially those related to injecting drug use [44]. Prisoners often have prevalence rates of antibodies to HCV comparable to those of IDUs due to a high proportion of IDUs among this group [46][47][48][49][50][51][52][53][54]. In Germany, Spain and in UK the anti-HCV prevalence in sex workers ranged from 0.7 to 9.0 %; with the lowest estimate in Germany [20,23,24].…”
Section: T a B L E 4 Characteristics Of Hepatitis C Surveillance Systmentioning
confidence: 99%
“…However, new infections still occur at high rates in other at-risk populations, especially injection drug users (IDU). Worldwide, the prevalence of HCV infection among IDU ranges from 25% to 80% (14,21,22,27,34,45), and the incidence among younger IDU ranges from 9% to 38% per year (13,16,23,37,49).Monitoring HCV infection has principally been limited to serosurveys detecting HCV-specific antibodies (anti-HCV), using enzyme immunoassays (EIAs) and confirmatory recombinant immunoblot assays (RIBAs). However, these cannot differentiate between acute, recent, chronic, and resolved infections, distinctions which would be very useful for HCV surveillance.…”
mentioning
confidence: 99%